Spatial distribution of silica fillers in phase‐separated rubber blends investigated by three‐dimensional elemental mapping. Issue 45 (27th July 2021) - Lyu, Lingyun; Hanada, Takeshi; Yamahira, Naohiro; Morita, Jun; Yamamoto, Ryota; Itomi, Ken; Adachi, Takumi; Kubouchi, Sho; Horiuchi, Shin
Abstract: The distribution of nano‐sized silica in binary rubber blends is characterized by scanning transmission electron microscopy (STEM) tomography combined with energy dispersive X‐ray spectrometry (EDX). 3D distribution of silica is visualized by STEM‐EDX tomography with the tilt‐series of silicon elemental maps, while the phase‐separated morphologies of polyisoprene rubber (IR) and styrene‐butadiene rubber (SBR) are visualized by STEM‐tomography in high‐angle‐annular‐dark field (HAADF) mode. The combination of STEM‐EDX and STEM‐HAADF tomography enables us to determine the distribution of silica between the two rubber phases quantitatively even with high contents of silica up to 70 phr (weight parts per hundred rubber). It is found that silica is preferentially distributed in the SBR phase, but it is also distributed in the IR phase when the IR fraction in the total rubber components is higher than 40 wt%. The preferential distribution of silica in the SBR phase improves the dispersion of the IR domains. This is the first use of this technique for a multicomponent polymer system, showing the advantage to characterize the complicated multicomponent polymer composite morphologies. Abstract : Spatial distribution of silica fillers in IR/SBR (70/30) rubber blends are quantitatively determined by three‐dimensional elemental mapping by means of STEM‐EDX tomography. The silica in IR (light blue) and in SBR (dark blue) phases can be identified as yellow and pink regions, respectively. The loading of large amount of silica produces the fine co‐continuous phase separated morphologies.